Analytical study of the most important water characteristics of some groundwater wells in the city of Al-Bayda - مجدي صالح خليفة; سامي سعد عريف; طيب الفرجاني طيب (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to evaluate some chemical and physical characteristics of groundwater from several wells distributed across different areas in the city of Al Bayda. The sampled wells were: "Groundwater/Niz Linizin", Al-Quds, Khadija, Teyarek, Al-Da’eri, Barshaira, and Kaf Shweikh. Chemical analyses were conducted on water samples to determine the concentrations of major ions (Sodium, Potassium, Magnesium, Calcium, Carbonate, Chloride, Bicarbonate, and Total Hardness) in addition to Nitrate (NO₃) and the heavy metals Lead, Iron, and Zinc. By comparing the obtained results with the Libyan Standard Specifications and the World Health Organization (WHO) guidelines, the study found that the values for the chemical and physical characteristics of the well water in the studied area generally fell within the permissible limits for drinking water. However, the values for Nitrate (NO₃) ranged between 16.7 and 77.7 mg/L. The highest value was recorded in the Barshaira wells (77.7 mg/L), followed by Al-Quds wells (60.36 mg/L). These levels exceed the permissible limits set by both the Libyan Standard Specifications and the WHO guidelines. In contrast, the values for heavy metals in the well water of the studied area were within the permissible limits for drinking water.